Uma investigação sobre o poder causal da informação em gerar conhecimento a partir da obra knowledge and the flow of information, de Fred Dretske - Bandeira, Francisco Dário de Andrade (2015)
The intensive demand for information nowadays confirms that information has an huge casual power. There’s a diversity of meaning of information and research approach, which can be explained by the different modes of occurrence of information, or even by the complexity of the term. Beyond these tensions, information is generally a valuable resource, a commodity, because it’s an essential element for generation of knowledge. But how information influences the human phenomena? How information contributes for generation of knowledge? This research aims to answer this question based on the work of Fred Dretske (1981). This philosopher proposed an informational semantic that explain how the immaterial side of information, which is related to perception, influences the generation of knowledge. Considering some aspects of mathematical theory of communication, Dretske presents information surrounded by a network of casual relations and nomic regularities that allows the receptor (a person able to understand properly a received message) to have full access to the events of an information resource. This study concludes that the Dretskian notion of information, despite the criticism for its probabilistic nature, once review, offers important insights that help us to understand how knowledge is created in different worlds of information.